Develop the ubiquitous computing wearable IoT devices using IoT-distributed framework - J. Ashok; S. Purushothaman; Purnendu Shekhar Pandey; K. Praveena; Chetan Pandey; J. Muralidharan (Measurement: Sensors, 2024)
Body Area Sensor Network (BASN) communication methods meet clients' multi-level requirements through Wearable Internet of Things (WIoT) systems. Transparency at management levels, heterogeneous support, and distributed communication to users are requirements of the PCS. Providing essential functions is a serious problem. A flexible Ubiquitous Computing (UC) architecture presented in this study is used to improve the reliability of end-user communication in the WIoT-based health sensor approach. According to this method, demand and sharing variables provide the foundation for the evaluation of resource allocation through recurrent learning. A proposed method could be used to implement end-user mobility management on WIoT healthcare sensors for data transmission, resource allocation and sharing. To show the integrity of the approach, some parameters were used in the actual evaluation and performance predictions. In the ubiquitous ecosystem, the uninterrupted flow was guaranteed to reduce the likelihood of a request being blocked. Memory control to density assignment at the framework level through storage management helps reduce backlogs and failures when allocating resources. The proposed approach enhances storage utilization, bandwidth, and request management besides lowering connection speed, backlogs, and request failure compared to the existing systems.